A facilitated natural mentoring program: Young adults with autism learn to negotiate college life in a class with university students - Cook, Barbara; Weiss, Deborah; Hodge, Virginia (The ASHA Leader, 2017)
Young adults with autism learn to negotiate college life in a class with university students. © 2017 American Speech-Language-Hearing Association.
3 citations (Crossref) [2023-10-31]
Keywords: dept.cmd